TEACHING PERSUASIVE TEXTS THROUGH THINK-TALK-WRITE (TTW) STRATEGY: AN INSTRUCTIONAL ANALYSIS - isah cahyani (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
Abstract This research was conducted after noticing the writing problems occurred in grade VIII of one public junior high school in Bandung in academic year 2017/2018. The students showed their inability of writing persuasive texts in accordance with the generic structures and language uses. The treatment used to overcome the problem was think-talk-write (TTW) together with the application of video as the instructional media. The research foci were: 1) how the learning session with TTW strategy was planned and was conducted; 2) how the improvement of students’ learning outcome by using TTW with video media was; 3) how the students’ responses towards the use of TTW with video media were. The research aimed at equipping the students with the ability to write persuasive texts appropriately. The method employed was classroom action research conducted in three cycles. The data collection techniques used were tests, observations, and questionnaires. The data were analyzed through several steps: categorizing, interpreting and validating data. The result indicated that learning to write persuasive texts by using TTW with video media improved the students’ writing ability. This was pointed by the test result from all cycles; in cycle I, the mean of students’ scores was 63; in cycle II, it increased to be 72; and in cycle III, it showed improvement to be 81. To conclude, it was proved that TTW strategy could improve the students’ writing ability on persuasive texts. Keywords: writing, persuasive texts, learning strategy, instructional media